The Effects of Property Relations on Urban Renewal Project - Yakup Egercioglu (European Regional Science Association (ERSA), 2006)
The concept of property, since the beginning of its existence, has played a fundamental role in social life both in physical and moral aspects. That is the point where the issue becomes that much important. In Turkey especially for the last 40 years there has been a massive migration from the rural areas to the urban ones. In parallel with this rapid urbanization, it has been reported by the DIE (State Statistics Institution) that Turkey's population increase rates are expected to decrease gradually and by the 2050's the total population is expected to reach and stabilize as 100 million people. This projection of a stable population structure, government policies aligned with this projection, for example issues taken into the agenda like the renewal of the "gecekondu" areas within the next 10 years; these are all some certain clues for the forthcoming stabilization of the urban improvement and future significance of the concept "urban renewal". For this reason the research will focus on the concept "property" which is an effective factor in the urban renewal projects. Property ownership is the most important parameter we face while working on urban renewal projects. Readjustment of property relations imposes certain responsibilities upon the planner. However within the planned period, Development Acts do not envisage an obligation for the planner regarding the matter of property during the preparation of development plans. Furthermore, legislation creates unequal states and makes it extremely hard to readjustment of the property relations and to implement development plans. Preparation process and implementation stage of the development plans are executed in the same manner traditionally. In brief, this proposal, assuming that the preparation and implementation processes of the plans will stay same, studies the effects of urban renewal projects on the property relations and makes suggestions. In brief, for the last 40 years there has been a development plan challenge in Turkey. Plans made without taking the social requirements and demands into consideration are continuously amended via revising localized development plans and results are strange even to the planner himself. Enacted construction pardons have increased the density on the urban areas and invalidated the prepared plans. In such an environment some immovable owners are rewarded while others are fined in a way. For that reason following measures shall be taken: Concepts of permanent or temporary utilization right and habitation right shall be discussed with a new property definition perspective. Besides regulations must be issued concerning the prevention of land value increases through development plans. Turkey's development acts shall be revised and legislation creating unequal status regarding the property rights shall be abrogated. A new development plan technique, urban design projects and semi public sphere concepts shall be adopted.
Keywords: 330